Village Government Communication Strategy in Coffee Farmer Community Empowerment Activities in Tanjung Beringin Village, South Merapi District, Lahat Regency - Ellia Surista; Taufik Akhyar; Chairunnisah Putri Ayu Ningsih (Universitas Muhammadiyah Palu, 2026)
This study aims to analyze the communication strategy of the village government in the empowerment of the coffee farmer community in Tanjung Beringin Village, South Merapi District, Lahat Regency, and identify communication obstacles faced in its implementation. This study uses a qualitative approach with a descriptive method. Data collection techniques were carried out through in-depth interviews with key informants, field observations, and documentation. The results of the study show that the village government implements various communication strategies, namely interpersonal communication (face-to-face), communication through the media (WhatsApp), participatory communication, extension communication (educational), plot demonstration (demonstration plot), and communication based on local culture. Of all these strategies, face-to-face communication is the most dominant and effective because it is able to adapt to the characteristics of the farming community. Meanwhile, the use of digital media serves as a support in the dissemination of information. Participatory communication strategies, counseling, and plot demonstrations have been proven to be able to increase farmers' understanding, skills, and trust in the innovations provided. However, in its implementation, there are still various communication barriers, such as obstacles in message delivery, physical obstacles, low community participation, resistance to change, and cultural and customary barriers. Therefore, a more adaptive, participatory, and in accordance with the socio-cultural conditions of the community is needed so that the empowerment process can run more optimally.